Importance of nest sites availability for abundance and changes in number of House and Tree Sparrow in Warsaw - Węgrzynowicz, Andrzej (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
House- and Tree Sparrows were censused on 55 plots (684 ha), representing 3 habitats: housing estates, parks and allotment gardens in Warsaw from 2005-2009 and in 2012. Also, the data on nest sites of both species were gathered. Data from 70s/80s of the other authors enabled to determine the changes in number of sparrows. The population of House Sparrow decreased on average by 48% and the sharpest decline was found in allotment gardens. The decline continued in the period of studies, i.e. in 2005-2012.
Keywords: House Sparrows; Tree Sparrow; breeding densities; population dynamics; changes in number; nest sites